2021
DOI: 10.1016/j.tem.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrating metabolic reprogramming and metabolic imaging to predict breast cancer therapeutic responses

Abstract: Metabolic reprogramming is not only an emerging hallmark of cancer, but also an essential regulator of cancer cell adaptation to the microenvironment. Metabolic imaging targeting metabolic signatures has been widely used for breast cancer diagnosis. However, limited implications have been explored for monitoring breast cancer therapy response, although metabolic plasticity is notably associated with therapy resistance. In this review, we focus on the metabolic alterations upon breast cancer therapy and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 89 publications
(162 reference statements)
0
13
0
Order By: Relevance
“…For preclinical animal studies, metabolomic profiling of tumour tissue harvested at necropsy is a suitable alternative. Metabolic imaging modalities that enable tissue localization of exogenous metabolites, such as PET tracing of 18 F-labelled metabolites and MRI tracing of 13 C-labelled metabolites, represent another powerful tool to characterize the tumour and systemic host response to nucleotide synthesis inhibitors 156,157 .…”
Section: Target Engagement Monitoringmentioning
confidence: 99%
“…For preclinical animal studies, metabolomic profiling of tumour tissue harvested at necropsy is a suitable alternative. Metabolic imaging modalities that enable tissue localization of exogenous metabolites, such as PET tracing of 18 F-labelled metabolites and MRI tracing of 13 C-labelled metabolites, represent another powerful tool to characterize the tumour and systemic host response to nucleotide synthesis inhibitors 156,157 .…”
Section: Target Engagement Monitoringmentioning
confidence: 99%
“…To our astonishment, TLS‐positive and TLS‐negative immune cells had entirely different metabolic pathways (Figure 7C). The tricarboxylic acid cycle (TCA cycle), glycolysis, and fatty acid production were all significantly increased in TLS‐negative tumours, and activation of these metabolic pathways is assumed to be closely related to carcinogenesis, progression and drug resistance 43 . We concentrated on the TCA cycle, glycolysis, fatty acid biosynthesis, oxidative phosphorylation and amino acid metabolism in BC immune cells to further investigate the metabolic differences in various states of TLSs (Figure 7D), as metabolic reprogramming grants cancer cells the ability to survive and proliferate, a key factor in tumour development 44 .…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the activity of metabolic enzymes in saliva in breast cancer patients was an interesting fact (Table 2). An increase in the activity of LDH, the final enzyme of anaerobic glycolysis, was natural due to an increase in glycolysis along with a low efficiency of mitochondrial oxidation in breast cancer [49,50]. Several studies have shown that overexpression of ALP may be associated with metastatic processes in cancers, including breast cancer [51,52].…”
Section: Discussionmentioning
confidence: 99%